'Happy birthday Grandpa'. (3rd August 2018) - Busch, Gillian Roslyn
Abstract : Video-supported technology is employed by many families to support familial relationships between grandchildren and grandparents. Employing an ethnomethodological and conversation analytic approach, this paper investigates the interactions of one family during a Skype session. The Skype call examined has special significance as the family members (mother and grandson) are calling to celebrate Grandpa's birthday. Detailed examination of video-recorded intergenerational interactions shows how the interactions are managed. Analysis highlights the important role of the mother in managing the progression of the call and her child's interaction with the grandfather. The interactional resources employed by the grandfather to initiate and sustain interaction with his grandson are examined. Also explicated is the interactional competence of a very young child in deploying interactional resources that orient to the affordances of technology. The findings contribute to understandings about how intergenerational interactions occur.